People strategy : how to invest in people and make culture your competitive advantage - Altman, Jack (New Jersey & Canada John Wiley & Sons, 2021)
"The rise of technology and the information age has resulted in more companies that compete primarily based on their people. And it's no surprise that people-centric companies are the ones winning the talent war. And that's because people-centric companies invest in People Strategy. People Strategy provides a unique framework for executive, HR, and team leaders to use data to build company culture, increase employee motivation, and drive high-performing teams. The book will guide the reader through: establishing the values that will be the bedrock of your culture; show the feedback components that help employees feel heard, supported, and equipped to succeed; explain ways to monitor the temperature of employee engagement; and ultimately how to use the data and insights to ensure your People Strategy is showing business results. Each section will feature Lattice's best practices and how-to advice, and will also feature stories from leaders from companies like Salesforce, Stripe, and Google to help demonstrate how our system is working in the real world."
Includes bibliographical Index
nmn, 23/12/2022
Loans
Keywords: Personnel management; Corporate culture; Management and Business Studies; People strategy; Competitive advantage